The effect of short stories on secondary school students’ reading comprehension skills and attitudes in Northwest Ethiopia - Yewulsew Godie Gela; Birtukan Gizachew Ayal (PLoS ONE, 2026)
Background Reading comprehension is a critical skill for English as a foreign language learner. However, many Ethiopian secondary school students have been having trouble in reading comprehension, where English is a medium of instruction. Therefore, this study examined the impact of short stories on secondary school students’ reading comprehension and assessed their attitude towards short stories. Methods A quasi-experimental design was employed. The participants were two sections of 9 th graders (n = 120) that were randomly assigned to experimental (n = 60), and control (n = 60) groups. The data were collected through a pre-and post-intervention reading comprehension test and an interview. Quantitative data were analyzed using independent and paired samples t-tests with effect sizes reported to strengthen statistical interpretation. Qualitative data were collected through interview with seven experimental group participants and analyzed thematically. Results Results showed no significant difference between groups at pretest in their reading comprehension skills (t = 0.32, df = 118, p = 0.75). The post-test results showed that the experimental group (m = 10.38, sd = 2.63) significantly outperformed the control group (m = 6.72, sd = 2.57, p = 0.001). Within- groups analysis confirmed that the control group showed no significant change (p = 0.57). However, the experimental group showed significant change in reading comprehension test performance (p = 0.01). Interview findings displayed that short stories improved reading comprehension skills and fostered a positive attitude toward reading. Conclusion The integration of short stories into English foreign language reading instruction significantly enhanced students’ reading comprehension skills. It also increased students’ positive attitudes in the reading texts. Therefore, it is recommended that English foreign language teachers should supplement reading skills instruction with culturally relevant short stories, and curriculum developers should incorporate more short stories in grade nine English textbooks to develop students’ reading comprehension skills.